Penerapan hasil belajar dribbling permainan sepak bola melalui variasi media audiovisual pada siswa kelas V SD Swasta Islam Terpadu Arisa - Zebua, Agung Trysman; Gulo, Amos Fransiskus; Al Hasan, M. Iqbal; Taryatman, Taryatman; Winata, Devi Catur; Rudiyanto, Rudiyanto (Universitas Sarjanawiyata Tamansiswa, 2025)
: This research aims to find out how to improve the learning outcomes of dribbling in soccer games through audiovisual media for fifth grade students at Arisa Integrated Islamic Private Elementary School in 2023/2024. The time of the research was carried out in July 2024. The objects of this research were class V students with a total of 25 students consisting of 13 male students and 12 female students who would be given action in the form of audiovisual media. Based on the student learning results in the first cycle, the first learning results test was carried out. It can be seen that the students' initial abilities in performing dribbling techniques were still low. Of the 25 students, 10 people (34%) have achieved learning completeness, while 15 people (66%) have not yet achieved learning completeness. The average student learning outcome score is 76.3. Meanwhile, in cycle II it can be seen that students' ability to carry out classical learning outcomes tests has increased. Of the 25 students, 20 people (86.2%) have achieved learning completeness, while 5 people (13.8%) have not yet achieved learning completeness. With the average student learning outcome score being 80.7, there is a 25% increase in learning outcomes from cycle I to cycle II. Based on this, it can be concluded that learning through variations in Audiovisual Media Learning can improve dribbling learning outcomes for fifth grade students at the Arisa Integrated Islamic Private Elementary School for the 2023/2024 academic year.